Corporate Financial Performance in the Wake of ESG Controversies: The Indian Firm Context - Mannu Dutt; Riidhi Jain; Dipasha Sharma; Sonali Bhattacharya (Australasian Accounting, Business and Finance Journal, 2025)
This study investigates the influence of ESG disclosure scores and ESG controversies scores on the financial performance of NSE 500 companies from 2020 to 2024. The analysis focuses on key financial metrics, including Return on Assets (ROA), Return on Equity (ROE), Price-to-Earnings (PE) ratio, and Tobin’s Q. The results indicate a significant positive relationship between ESG disclosure scores and both ROA and ROE, suggesting that transparent ESG reporting enhances organisational efficiency and financial outcomes. These findings align with Freeman’s Stakeholder Theory (1984) and earlier studies of Kumari et al. (2022), which posits that engaging stakeholders through transparent ESG disclosures improves financial results. The results carry important implications for both corporate managers and investors. For managers, the positive association between ESG disclosure scores and financial performance highlights the importance of transparency in ESG reporting. While ESG controversies may not have immediate financial effects for investors, they could harm long-term financial performance and corporate reputation. By examining the dual role of ESG disclosure and controversy scores, this study seeks to provide valuable insights for corporate managers and investors, emphasising the critical importance of transparency and ethical conduct in enhancing organisational trust and financial outcomes.
Keywords: ESG disclosure scores; ESG controversies; Financial performance; Corporate reputation; India